2010
DOI: 10.1111/j.1740-8261.2009.01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Diagnosis—left Retrocaval Ureter and Transposition of the Caudal Vena Cava in a Dog

Abstract: Retrocaval ureter and transposition of the caudal vena cava are each, rare developmental anomalies. We describe the usefulness of static fluid magnetic resonance urography and dynamic contrast-enhanced magnetic resonance urography in the diagnosis of these anomalies. Basic techniques, benefits, and drawbacks of magnetic resonance urography are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 16 publications
4
27
2
Order By: Relevance
“…The imaging features of abdominal congenital vascular malformations, such as congenital portosystemic shunts, arterioportal malformations, azygos continuation of the caudal vena cava with and without concomitant portosystemic shunt, retrocaval ureter, caudal vena cava duplication, and caudal vena cava and portal vein aplasia, have been well described . In addition, MDCT anatomical criteria have been established for the diagnosis and classification of arterio‐portal malformation and a systematic “step‐by‐step” approach has been proposed for the ultrasonographic diagnosis of portosystemic shunts …”
Section: Introductionmentioning
confidence: 99%
“…The imaging features of abdominal congenital vascular malformations, such as congenital portosystemic shunts, arterioportal malformations, azygos continuation of the caudal vena cava with and without concomitant portosystemic shunt, retrocaval ureter, caudal vena cava duplication, and caudal vena cava and portal vein aplasia, have been well described . In addition, MDCT anatomical criteria have been established for the diagnosis and classification of arterio‐portal malformation and a systematic “step‐by‐step” approach has been proposed for the ultrasonographic diagnosis of portosystemic shunts …”
Section: Introductionmentioning
confidence: 99%
“…The left‐sidedness variant is rare in dogs and humans . Based on our review of the literature, this type has been published in only one dog, concurrent with a retrocaval ureter . This type of CVC is derived from the regression of the right supracardinal vein and the persistence of the left supracardinal vein .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only a few reports of canine CVC variants have been published. Duplication, transposition, azygos continuation, and segmental aplasia of the CVC and abnormal ureteral course affected by CVC transposition have been reported in dogs and cats . A previous study in dogs showed a prevalence of CVC duplication of 2.08% and a significant association between CVC duplication and extrahepatic portosystemic shunt .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[4] While the diagnosis of circumcaval ureter in an excreting kidney can be made by CTU or in a non-excreting kidney might be suggested by a non-contrast CT, this series of seven cases illustrates the ability of MRU to clearly depict relevant anatomic relationships and provide confirmatory diagnosis without radiation exposure or the use of contrast medium. To the authors’ knowledge, this is the largest series describing MRU findings of circumcaval ureter.…”
Section: Introductionmentioning
confidence: 99%